Recepce ideje státu jako šťastného domova v náboženských obcích Církve československé v Brně v letech 1948–1960 - Jakub Marša (Studia Historica Brunensia, 2022)
Years after February 1948 was a difficult period for the Czechoslovak Church. Although the ideologically divided church had a partially negative attitude towards the communist regime, another significant part of ordinary believers and priests (including church leadership) saw the communist state as an opportunity to fulfill the idea of Christian socialism. Czechoslovakia was to become a happy home for unbelievers and Christians alike. The paper is focused on the daily life of the religious communities of the Czechoslovak Church in Brno between 1948 and 1960. It seeks answers to the questions of how the vision of the coexistence of the communist state and the Czechoslovak Church was accepted among the believers themselves at the local level and how the relationship of believers to their new home developed during the dynamic 1950s.